Upaya Meningkatkan Hasil Belajar Siswa Materi Keliling Bangun Datar Menggunakan Model Pembelajaran Pair Check - Citra Cahyaningtyas (Universitas Kanjuruhan Malang, 2021)
This study aims to describe the process of implementing the pair check learning model and to describe the improvement of student learning outcomes in class IIIB SD No. 8 Jimbaran on the material around the flat wake. This research is a classroom action research with the research subjects of class IIIB elementary school students. 8 Jimbaran, totaling 23 students. This research was carried out in 2 cycles and each cycle consisted of planning, implementation, observation, and reflection stages. The data obtained in the form of student learning outcomes, student activity and teacher activity. The results of this study are the percentage of mastery learning outcomes has increased from 39.13% to 86.95%, while the results of observations of teacher activities obtained a percentage of 71.9%. The conclusions of this study namely the pair check learning model can significantly improve student learning outcomes that is equal to 86.95%.